Utilizing The Edu-Panda Application To Improve Personel And Academic Administration Services - Choironi, Mohammad Afif; Haq, Rosyida Rahmatul; Al Faini, Muhammad Baha’ul Alamsyah; Wahyudin, Aji; Zuhriyah, Indah Aminatuz (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Information and communication technology have influenced various aspects of life, including education. In the context of schools, using administration-based applications has become increasingly important to facilitate and enhance the efficiency of administrative processes. This abstract presents an overview of the utilization of the edu-Panda application in MAN 2 Kota Malang (a high school in Malang City) and its impact on the effectiveness of school administration management. This study aims to describe implementing an educational management information system (MIS) that includes utilizing management information systems and its implementation on administrative services at Madrasah Aliyah Negeri 2 Kota Malang. This research adopts a qualitative approach with a descriptive method. Data is collected through interviews, observations, and documentation as supporting evidence. Data analysis is conducted using qualitative techniques, including data collection, reduction, presentation, and conclusion. To ensure the validity of the data, the researcher employs triangulation techniques, including source triangulation and technique triangulation. The results of this study indicate that the planning of the edu-Panda application in Madrasah Aliyah Negeri 2 Kota Malang is based on the school's needs. After the system development is completed, a feasibility test is conducted before reaching the system installation phase. Thus, the system can operate according to its intended purpose. The implementation of the edu-Panda application in Madrasah Aliyah Negeri 2 Kota Malang can be used to track attendance, information, allowances, graduation, and matters related to personnel and academics. Based on the five dimensions of service quality used to assess and measure service quality in Madrasah Aliyah Negeri 2 Kota Malang, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy, the services in Madrasah Aliyah Negeri 2 Kota Malang are considered good. Keywords: Management Information System, edu-Panda, Staffing, Academic